Incentives For Workers As Intervening Variables On The National and Political Unity Agency (KESBANGPOL) Simalungun Regency - Jopinus Ramli Saragih (Journal of Governance, 2022)
This study aims to determine the effect of emotional intelligence and work motivation on employee performance with incentives as intervening variables (Case Study on National and Political Unity Agency Employees, Simalungun Regency, Pematang Siantar City). The research method used is the quantitative data method. Data collection in this study was carried out by distributing questionnaires (questionnaires) to respondents. The results of this study are 1) The emotional intelligence (X1) variable has a positive and statistically significant effect on incentives (Z).2) The Variable Work Motivation (X2) has no positive or significant effect on Incentives (Z).3) Emotional intelligence (X1) has a significant effect on employee performance (Y). 4) Work Motivation (X2) has a significant effect on Employee Performance (Y). 5) Incentives (Z) have a significant effect on employee performance (Y). 6) The incentive (Z) is an intervening variable that mediates the effect of emotional intelligence (X1) on employee performance (Y).7 Incentive (Z) is an intervening variable that mediates the effect of work motivation (X2) on employee performance (Y). This shows that emotional intelligence (X1) and work motivation (X2) can explain the incentive (Z) of 88.9%. This shows that the Incentive (Z) Emotional Intelligence (X1) and Work Motivation (X2) can explain Employee Performance (Y) by 65.2%. The author suggests that human resources or employees should prioritize the quality of emotional intelligence in addition to their intellectual intelligence so that there is a balance in terms of achieving good performance. In order for employees' work motivation to increase, the National Unity and Political Agency of Simalungun Regency Pematang Siantar City should increase the level of persistence of employees by paying attention and developing skills in order to advance the agency and improve employee performance. The incentive compensation system that is implemented should generate benefits for both parties, namely the National Unity and Political Agency of Simalungun Regency, Pematang Siantar City, as the provider of incentive compensation, and employees.